The Putative Virulence Plasmid pYR4 of the Fish Pathogen Yersinia ruckeri Is Conjugative and Stabilized by a HigBA Toxin–Antitoxin System - Fisentzos Floras; Chantell Mawere; Manvir Singh; Victoria Wootton; Luke Hamstead; Gareth McVicker; Jack C. Leo (Biology)
The bacterium Yersinia ruckeri causes enteric redmouth disease in salmonids and hence has substantial economic implications for the farmed fish industry. The Norwegian Y. ruckeri outbreak isolate NVH_3758 carries a relatively uncharacterized plasmid, pYR4, which encodes both type 4 pili and a type 4 secretion system. In this study, we demonstrate that pYR4 does not impose a growth burden on the Y. ruckeri host bacterium, nor does the plasmid contribute to twitching motility (an indicator of type 4 pilus function) or virulence in a Galleria mellonella larval model of infection. However, we show that pYR4 is conjugative. We also reveal, through mutagenesis, that pYR4 encodes a functional post-segregational killing system, HigBA, that is responsible for plasmid maintenance within Y. ruckeri. This is the first toxin–antitoxin system to be characterized for this organism. Whilst further work is needed to elucidate the virulence role of pYR4 and whether it contributes to bacterial disease under non-laboratory conditions, our results suggest that the plasmid possesses substantial stability and transfer mechanisms that imply importance within the organism. These results add to our understanding of the mobile genetic elements and evolutionary trajectory of Y. ruckeri as an important commercial pathogen, with consequences for human food production.